2005
DOI: 10.1016/j.visres.2004.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Visual and spatial symptoms in Parkinson’s disease

Abstract: The interaction of visual/visuospatial and motor symptoms in Parkinson's disease (PD) was investigated by means of a 31-item self-report questionnaire. The majority of 81 non-demented patients reported problems on non-motor tasks that depended on visual or visuospatial abilities. Over a third reported visual hallucinations, double vision and difficulty estimating spatial relations. Freezing of gait was associated with visual hallucinations, double vision and contrast sensitivity deficits. Visual strategies fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
200
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(213 citation statements)
references
References 84 publications
10
200
0
3
Order By: Relevance
“…Barnes et al [5] did not observe greater deficits in hallucinating PD patients on the spatial perception subtest of the Visual Object and Space Perception Battery than in nonhallucinating PD patients. However, other authors found an association between hallucinatory experiences and difficulty estimating spatial relations [27] and visuospatial learning [4] . The continuous deterioration on the Visual Form Discrimination Test in our hallucinating PD patients would suggest a visuospatial progressive decline in addition to a visuoperceptive dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Barnes et al [5] did not observe greater deficits in hallucinating PD patients on the spatial perception subtest of the Visual Object and Space Perception Battery than in nonhallucinating PD patients. However, other authors found an association between hallucinatory experiences and difficulty estimating spatial relations [27] and visuospatial learning [4] . The continuous deterioration on the Visual Form Discrimination Test in our hallucinating PD patients would suggest a visuospatial progressive decline in addition to a visuoperceptive dysfunction.…”
Section: Discussionmentioning
confidence: 85%
“…Hence, the basal ganglia may have a role during the co-regulation of force and timing of movement, especially when movement changes are required. It appears that freezing exemplifies a disruption of the co-regulation of timing and amplitude [15,32], no doubt brought on and magnified by multiple factors such as motor and postural adaptations [1] and visual/spatial deficits interacting with perception of the environment [35]. In addition, mental aspects [36] of emotional as well as cognitive origin and of which attention is possibly the most crucial factor [32,37], are considered contributory to lowering the threshold for the occurrence of freezing.…”
Section: Discussionmentioning
confidence: 99%
“…Visual, 47,48 emotional, and cognitive triggers 49,50 of which distraction is possibly the most crucial one, 49 contribute to lowering the threshold for the occurrence of FOG. It appears that FOG-episodes frequently come to the fore in situations when reliance on basal ganglia control is periodically increased and attention is allocated elsewhere.…”
Section: Attention and Fogmentioning
confidence: 99%